Oroclines in the Tasmanides. (November 2015) - Musgrave, Robert J.
Abstract: Oroclines are features of orogenic belts that exhibit curvature in plan on a map scale, with the additional requirement that this curvature resulted from relative rotation of the limbs around a vertical or near-vertical axis. Much debate has centred on contrasts between thin-skinned and thick-skinned systems, and on the question of whether the structural fabric was imposed prior to or synchronous with the development of curvature, leading to a variety of inconsistent terminology. A simple hierarchy, in which all map-scale curved orogenic features which pass a test for rotation are termed oroclines (as distinct from primary arcs), and in which these are then subdivided by timing into progressive (synchronous fabric and curvature) and secondary (pre-existing fabric is then rotated), and by mechanism into thin- or thick-skinned, is applied to a suite of curved orogenic features in the Tasmanides of eastern Australia. This analysis includes the first formal application of the "orocline test" (palaeomagnetic or palaeocurrent directions plotted against structural strike) to the Tasmanides. The Neoproterozoic to early Mesozoic Tasmanides comprise four orogens, each of which contains curved orogenic features which are highlighted by extensive aeromagnetic datasets. The Delamerian Orogen, developed on the Gondwana margin, exhibits two curved structures in the Neoproterozoic to Cambrian Adelaide Fold Belt, termed the Fleurieu and Nackara arcs: previous structural interpretations have indicated that the Nackara Arc is non-rotational, and hence not oroclinal. Re-examination of existing palaeomagnetic data, including a positive palaeomagnetic orocline test, shows the Nackara Arc to in fact be a hinge of the Adelaide orocline. Curvature in the Adelaide orocline was dominantly progressive and thin-skinned, but may have been influenced by secondary rotation of the pre-existing, partly underlying Curnamona Craton. Mega-kinks in a buried Delamerian arc-volcanic chain revealed in aeromagnetic images follow the curvature of the Nackara Arc, suggesting an accompanying thick-skinned, secondary oroclinal deformation further from the continental margin. Orogenic curvature in the Palaeozoic Lachlan Orogen has only been widely recognised since the advent of tilt-filtered aeromagnetic images, and a model of oroclinal folding with two hinges (Riverina and Tambo) and strike-slip offset during the Silurian Bindian orogeny has recently been proposed to explain perplexing repetitions of sequence and inversions of structural vergence and directions of sediment provenance. Palaeomagnetic data indicates rotation of elements within the proposed orocline, and a preliminary study indicates a positive palaeomagnetic orocline test for the Riverina hinge. Palaeocurrent data around the Tambo hinge provide a positive, if scattered, orocline test. An independently conceived numeric model of the roll-back response to congestion of a subduction zone has generated an oroclinal structure which shares many features with the proposed Lachlan orocline, and deep crustal ambient-noise seismic data confirms that the major curved and strike-slip features persist throughout the crust. The Lachlan orocline appears to be secondary and thick-skinned. Orogenic curvature in the largely covered Thomson Orogen occurs along its southern border with the Lachlan Orogen (the putative Olepoloko orocline) and around its geometrically complex boundary with the Mossman Orogen in northern Queensland (the Charters Towers orocline). Rotation of the Olepoloko structure cannot be confirmed, and competing models for its formation leave open the question of whether this is a primary arc, a thin-skinned progressive orocline, or a thick-skinned secondary orocline. Palaeomagnetic data from the Charters Towers orocline are limited to two poles, but a change in declination between the Silurian pole and the Devonian pole matches the apparent rotation of the orocline, which appears to have been thick-skinned and secondary. In contrast to the other orogens, consensus that at least part of the curvature in the Palaeozoic to Triassic New England Orogen is oroclinal has been broad, although not universal. There remains substantial debate over the number of hinges (from two to four) and mechanism. Palaeomagnetic poles have previously been cited as evidence of rotation of blocks within the orocline, but this paper presents the first formal palaeomagnetic orocline test, which is positive for the Manning and Texas hinges. A palaeocurrent orocline test of the Manning hinge, in younger rocks than the palaeomagnetic sample, is negative, constraining rotation in the southern, Manning hinge to the Carboniferous before 322 Ma, while rotation in the northern, Texas hinge appears to be latest Carboniferous or Permian. The existence of a Hastings hinge is questionable, but if real, its rotation also appears to be younger than that of the Manning hinge. Thick-skinned, secondary rotation of the hinges of the New England orocline appears to have been diachronous.